Design Fully Integrated Driver Circuit for Phosphorescent White Light-Emitting-Diode High Speed Real-Time Wireless Communication - Dong Yan; Xurui Mao; Sheng Xie; Jia Cong; Hongda Chen (IEEE Photonics Journal, 2019)
The data rate for visible light communication (VLC) with commercial phosphorescent white light-emitting diodes (LEDs) is very limited because the $-$ 3 dB modulation-bandwidth of these LEDs is only a few megahertz. To increase the modulation bandwidth, a new, fully integrated driver circuit is proposed in this paper. The integrated circuit chip consists of a pre-emphasis circuit unit, an adjustable remaining carrier-sweep-out circuit, and a power-MOSFET driver. Using this chip, the $-$ 3 dB bandwidth of phosphorescent white LED transmitters can be extended from 3 to 80 MHz. The best obtained transceiver baud rate is 112 Mbit/s for a distance of 1.5 m, and the bit-error-ratio is ${\text{1.04}}\,× \,10^{-3}$ , which meets the data-rate requirement for IEEE 802.3 100BASE-TX. The LED-driver circuit is manufactured in an UMC ${\text{0.18}}\,{μ }\text{m}$ CMOS process, and the chip area is ${\text{1052}}\ ×\ {\text{762}}\ {μ }\text{m}^2$ . This driver chip can be used in VLC systems with the following advantages: low cost, low power-consumption, compatible with standard CMOS technology, and high integration-density.